HASIL DESTILASI KERING BEBERAPA JENIS KAYU INDONESIA - Tjutju Nurhayati Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The chemical degradation of wood products obtained by destructive distillation in this experiment are charcoal, pyroligneous liquor, wood tar and fuel gas. Pyroligneous liquor contains mainly water, acetic acid and methanol. Wood tar is very complicated phenolic compound and contains creosote oil and pitch.The results of destructive distillation of 45 wood species from East Kalimantan, lrian and Maluku vary widely. Charcoal yield ranged from 19.81to 41.24 percent, pyroligneous liqour from 40.29 to 66.12 percent and the yield tar from 5.42 to 20.60 percent. Chemical composition of the distillates indicated that acetic acid content ranged from 1.19 to 9.53 percent, methanol ranged from 0.22 to 3.75 percent, phenol ranged from 0.10 to 1.62 percent and pitch ranged from 2.06 to 11.53 percent.The result of proximate analysis of charcoal indicated that moisture content ranged from 1.12 to 6.85 percent, vovalite matter from 11.29 to 29.20 percent and ash ranged from 0.23 to 7.11 percent.